Abacus evolve 2: textbook - Merttens, Ruth; Kirkby, David (Ginn Harlow, 2007)
Teachers who use Abacus Evolve have praised its flexible assessment, planning support, creative teaching and sound mathematical progression. They tell us that this has helped them raise standards, reduce workload and increase confidence in maths.